2009
DOI: 10.1017/s0022377808007411
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of two-dimensional magnetic electron drift vortex mode turbulence in plasmas

Abstract: Abstract. Simulations are performed to investigate turbulent properties of nonlinearly interacting two-dimensional (2D) magnetic electron drift vortex (MEDV) modes in a nonuniform unmagnetized plasma. The relevant nonlinear equations governing the dynamics of the MEDV modes are the wave magnetic field and electron temperature perturbations in the presence of the equilibrium density and temperature gradients. The important nonlinearities come from the advection of the electron fluid velocity perturbation and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The spectral and statistical properties [21], as well as the generation of large scale magnetic fields [22] by the MEDV mode turbulence, have been investigate both theoretically and numerically. The generation of steep, nonKolmogorov spectra of streamer-like structures by MEDV turbulence has been observed in recent simulation studies [23].…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…The spectral and statistical properties [21], as well as the generation of large scale magnetic fields [22] by the MEDV mode turbulence, have been investigate both theoretically and numerically. The generation of steep, nonKolmogorov spectra of streamer-like structures by MEDV turbulence has been observed in recent simulation studies [23].…”
Section: Introductionmentioning
confidence: 73%
“…(1) can be contrasted with our previous work [23] on the small amplitude case that was studied in the absence of a background magnetic field gradient. In Ref [23], we have shown that mode coupling interactions during the nonlinear stage of evolution leads to the formation of streamer-like structures in the magnetic field fluctuations associated with ky ^0,kx^ 0. These structures were similar to the zonal flows but contained a rapid kx variations, thus the corresponding frequency is relatively large.…”
Section: Nonlinear Simulationsmentioning
confidence: 86%
See 3 more Smart Citations